1976
DOI: 10.1042/bj1540613
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of phenylalanine hydroxylase in rat tissues in vivo. The maintenance of high plasma phenylalanine concentrations in suckling rats: a model for phenylketonuria

Abstract: Maximum inhibition of phenylalanine hydroxylase activity in the liver (85 %) and in the kidney (50%) of suckling rats required the administration of over 9,pmol of p-chlorophenylalanine/lOg body weight. Despite the decrease in the total activity from 184 to 34 units per lOg body weight, the injection of as much as 26fmol of phenylalanine was required for its concentration in plasma to be still considerably elevated 12h later. In rats injected with p-chlorophenylalanine every 48h and with phenylalanine every 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1976
1976
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…The significant difference between day 21 control and PA rats in the trends of daily body weight increments (from days 3 to 21) reaffirms earlier reports of retarded body growth in rats subjected to experimental PKU [5,27], A 20% decrease in mean body weight ( fig. 1) between control and PA rats at day 21 is in contrast to the 60% decrease noted at day 20 in rats undernourished from birth [22], Hence the body weight deficits in the PA rats are more likely to reflect the effects of PA treatment than of undernour ishment.…”
Section: Somatic Considerationssupporting
confidence: 88%
“…The significant difference between day 21 control and PA rats in the trends of daily body weight increments (from days 3 to 21) reaffirms earlier reports of retarded body growth in rats subjected to experimental PKU [5,27], A 20% decrease in mean body weight ( fig. 1) between control and PA rats at day 21 is in contrast to the 60% decrease noted at day 20 in rats undernourished from birth [22], Hence the body weight deficits in the PA rats are more likely to reflect the effects of PA treatment than of undernour ishment.…”
Section: Somatic Considerationssupporting
confidence: 88%
“…Although subcutaneous or intraperitoneal injections of phenylalanine plus cr-methylphenylalanine have been our usual method of inducing severe hyperphenylalaninemia (12,21,25), some observations on 22-33-day-old rats indicated that similar results could be obtained by the incorporation of these substances into solid food (11). To avoid daily injections, this diet (see "Materials and Methods") was given to pregnant rats.…”
Section: Resultsmentioning
confidence: 99%
“…The assay of hepatic phenylalanine hydroxylase (E.C. 1.14.16.1) was as described by DelValle and Greengard (12). Protein was measured by the method of Lowry, et a1 (34) and DNA by the procedure of Kissane and Robins (27) as modified by Hinegardner (23).…”
Section: Animalsmentioning
confidence: 99%
“…served the practical purpose of creating hyperphenylrelationship between the amount of ingested phenylalaninaemic rats are described-in the preceding paper alanine and the concentration of this enzyme; they (DelValle & Greengard, 1976). reported that -in rats maintained on a low phenyl-McGee et aL.…”
mentioning
confidence: 99%
“…prompted-.by an. accidental observation; in experiments designed to maintain high concentrations of MaealanMthd phenylalanine in the plasma of immature rats [see the MaeilanMthd preceding paper (DelValle & Greengard, 1976)] we The animals used and the preparation of the noted that the recovery of phenylalanine hydroxylase phenylalanine and p-chlorophenylalanine suspension after inhibition by p-chlorophenylalanine in vivo was to be injected were as described in the precedinig'pape greatly hastened by injections of phenylalanine.…”
mentioning
confidence: 99%